Stakeholder Governance, Competition and Firm Value - Franklin Allen; Elena Carletti; Robert Marquez (Center for Economic Studies and ifo Institute (CESifo), 2014)
In many countries, the legal system or social norms ensure that firms are stakeholder oriented. We analyze the advantages and disadvantages of stakeholder-oriented firms that are concerned with employees and suppliers compared to shareholder-oriented firms in a model of imperfect competition. Stakeholder firms are more (less) valuable than shareholder firms when marginal cost uncertainty is greater (less) than demand uncertainty. With globalization shareholder firms and stakeholder firms often compete. We identify the circumstances where stakeholder firms are more valuable than shareholder firms and compare these mixed equilibria with the pure equilibria with stakeholder and shareholder firms only. Finally, we analyze firm financial constraints and derive implications for the capital structure of stakeholder firms.
Keywords: G32; L21; L22; 330